Produksi bio-oil dan bio-arang dari mata kayu industri pulp melalui pirolisis [Production of bio-oil and bio-char from knot in pulp mill through pyrolysis] - Syamsudin Syamsudin (Kementerian Perindustrian, 2019)
Acacia mangium knotis one of the biomass reject produced from the wood chemical pulping processes. This raw material is suitable for the production of bio-oil and bio-char in competitive costs. Utilization of the knot for the production of bio-oil and bio-char makes pulp mill as a bio-refining system with many profitable products because of increased income from bio-oil and bio-char and reduced costs for solid waste disposal. This study aims to evaluate the pyrolysis of knots from the kraft pulp mill to produce bio-oil and bio-char. Pyrolysis experiments of Acacia mangium knotwere carried out using laboratory-scale fluidized bed reactors at 400oC for 30 minutes. Acacia mangium knot contains volatile matterof 69.90% (dried basis) with a calorific value of 4279 kcal/kg (dried basis) has potency to produce bio-oil through the pyrolysis process. The TG-DTG analysis with heating rate of 10oC/min showed the pyrolysis reaction at temperature of 200oC-750oC resulting in a mass decreasing from 90% to 30% or around 85% of total conversion. The yield of bio-oil from fast pyrolysis was about 47%. Bio-oil contains high various organic compounds and dominated by acetic acid (21%) and 2-propanone (28%), and produced bio-char with a calorific value of 5763 kcal/kg (dried basis). Bio-char products could be used as a solid fuel in the combustion process or gasification process.